Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together Berbantuan Alat Peraga Sederhana Terhadap Hasil Belajar Fisika Siswa Kelas XI - Septina Severina Lumbantobing (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2017)
The research aim to know the influence of cooperative learning model NHT aided props to the learning outcomes of students in the subject matter physics kinematics with vector analysis. The method used is a quasi-experimental research design with pretest posttest control group design. This research was conducted in SMA Angkasa 1 Jakarta XI in the academic year 2016/2017. Sample studies class XI-2 as the control class and class XI-3 as the experimental class with cluster random sampling technique. Instruments used multiple choice that has been tested for validity and reliability. The results of this study concluded that cooperative learning NHT aided simple props affect the learning outcomes of students in the material physics kinematics with vector analysis. This can be seen from the calculation results of hypothesis testing via t-test at a significance level of 5% and dk = 66 result Sig. (2-tailed) <0.05, so it can be stated that Ho refused and Ha is received and also the results showed an average gain of 55% experimental class and control class 20%. This is also supported high student activity. The percentage of student activity experimental group included active category of 94% and 6% inactive category. while the control class that includes active category of 67.5% and 32.5% inactive category. The response of students to cooperative learning model NHT aided simple props reach 92%. Keywords: learning outcomes, cooperative learning, model NHT, props